Superior articular muscle syndrome - Siderman, Miguel Angel (Headache Medicine, 2011)
A high percentage of people of every age sufer, sickness, headache and symptomatology in the neck, waist, arms and hands. The Medical Institution diagnoses these symptoms as chronic sickness, and it limits to fight the symptomatology with analgesic, anti-inflamatorys and muscular relaxings who the patient consume-regularly during years. We interpret of all these regions belong to a same system, that we call Upper Articulated Muscle (UAM ). Jaw is the phisiological centre of itself. This certify the functions which take part phonation, swallowing and mastication, the movement that it executes, and a large number of muscles which inserts in it. The eccentric positions in the functions and in the rest modify the sincronization´s system determining the symptomatology appearance in one or several regions which compose the system. All these associated symptoms in a same cause characterize the syndrome.The conclusion of this clinical job here presented show the related symptons and the percentages of protrude of themselves.